(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2016)
Background: Breastfeeding reduces incidence of common childhood illnesses such as diarrhea and thus reduces infant mortality and morbidity. Objective: To find out the incidence of diarrhea in breastfed versus formula fed baby. Methodology: An observational cross sectional study was carried out in the Pediatric department of Northern private medical college hospital, Rangpur from March 2013 to June 2014. Total 150 children aged 1 to 24 months having diarrhea were enrolled in the study. Result: Mean age of children was 11.6 with SD ±5.29 months, ranges from 1 month to 23 months in which exclusively breast fed 51.3%, breast fed plus formula fed 39.3%, exclusively formula fed 9.4%; single attack of diarrhea occurred in 72.7%, 40.7%, and 28.6% children in exclusively breast fed, breast fed plus formula fed and exclusively formula fed children respectively. Frequent attack of diarrhea occurred in 27.3%, 59.3% and 71.4% children in exclusively breast fed, breast fed plus formula fed and exclusively formula fed children respectively; among 59 patients who developed first attack of diarrhea by 6 months of age, 10.2%, 69.5 % and 20.3% were from exclusively breast fed, breast fed plus formula fed and exclusively formula fed children respectively. Patients who developed first attack of diarrhea by 7-12 months of age, 69.8% were from exclusively breast fed, 27.0% from breast fed plus formula fed and 3.2% from exclusively formula fed children. But 28 children whose first diarrhea occurred by 13-24 months of age, 96.4% and 3.6% were from exclusively breast fed, and breast fed plus formula fed group respectively. Conclusion: Breast feeding reduces incidence of diarrhea, prevents frequent attack and early occurrence of diarrhea in under two children. J Bangladesh Coll Phys Surg 2016; 34(1): 21-25